Exploring EFL Students’ Perceptions of Translanguaging in Academic Writing Instruction in higher education - Diah Yovita Suryarini; Him’mawan Adi Nugroho; Amiruddin Hadi Wibowo; Yeskiel Timothy Barnez (PANYONARA: Journal of English Education, 2026)
This study aimed to examine EFL students’ perceptions on the use of translanguaging in academic writing instruction in higher education context. This study is a case study and using quantitative survey design with four-point Likert-scale questionnaire covering five dimensions of perceptions; understanding the writing material, the writing process, affective aspects, the role of translanguaging in academic learning, and challenges and limitations of its use. The absence of neutral option on the Likert scale encourages respondents to actively position their attitudes towards translanguaging practices. The result showed that students had consistently positive perceptions on the use of translanguaging in academic writing instruction. Translanguaging was perceived as aiding understanding of academic material, supporting the development and organization of ideas during the writing process and playing a role in cognitive and metacognitive regulation, such as planning, monitoring, and revising writing. From an affective perspective, translanguaging contributed to reducing writing anxiety and increasing students’ self-confidence and motivation to learn. Furthermore, students did not perceive translanguaging as a barrier to the development of their English language skills.